Factors associated with HIV infection and the utilization of HIV testing services among transgender people in Georgia. - Maka Gogia; Mark H Kuniholm; Pavlo Smyrnov; Jack DeHovitz; Tamar Zurashvili; Mamuka Djibuti (PLOS Global Public Health, 2025)
We assessed factors associated with HIV infection as well as the utilization of HIV testing among transgender people (TGs) in the country of Georgia. From July 2020 to January 2021, TG participants were recruited using snowball sampling in three major Georgian cities: Tbilisi, Batumi and Kutaisi. The participants underwent structured face‒to-face interviews and rapid tests for HIV. The study employed descriptive analyses, and bivariate and multivariable logistic regression to explore factors associated with HIV infection and HIV testing history. Of the 95 participants, 49.5% identified as transgender women, 7.3% as transgender men, and 43.2% as non-binary individuals, with a mean age of 27.24 years (SD = 8.52). Overall, HIV prevalence was 24.1%, with transgender women experiencing the highest burden (40.5%). HIV prevalence was higher among transgender women (40.5%) and those involved into commercial sex work (41.7%), however, none of the predictor variables reached the level of significance in adjusted model. HIV testing in the past six months were reported by 76.8% of participants and predictors for testing were living alone (aOR=5.9, 95% CI: 1.06-32.69) and experiences of enacted stigma (aOR=1.76, 95% CI: 1.04-2.97). Conclusion: Our study reveals a high HIV burden among transgender individuals in Georgia, particularly transgender women. This is combined with significant gaps in the utilization of HIV prevention services. Further research is needed to explore the intersection of stigma and other barriers affecting a low uptake of HIV testing to inform the development of effective targeted interventions.